1999
DOI: 10.1007/s004399900191
|View full text |Cite
|
Sign up to set email alerts
|

Two novel mutations of SURF1 in Leigh syndrome with cytochrome c oxidase deficiency

Abstract: Cytochrome c oxidase (COX) deficiency is the most common cause of Leigh syndrome (LS). COX consists of ten nuclear-encoded and three mtDNA-encoded structural subunits. Although the nucleotide sequences of all 13 genes are known, no mutation was found in nuclear-encoded subunit genes of COX-deficiency patients. Zhu et al. (1998) and Tiranti et al. (1998) found nine mutations in the surfeit 1 (SURF1) gene in LS families with COX deficiency. The mouse surfeit gene cluster consists of six closely spaced housekeepi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 9 publications
3
16
1
Order By: Relevance
“…However, approximately a third of our SURF1-deficient muscle specimens (and the remaining two reports of ultrastructural findings in the literature)7 8 did not demonstrate any ultrastructural anomalies of the mitochondria.…”
Section: Discussioncontrasting
confidence: 43%
“…However, approximately a third of our SURF1-deficient muscle specimens (and the remaining two reports of ultrastructural findings in the literature)7 8 did not demonstrate any ultrastructural anomalies of the mitochondria.…”
Section: Discussioncontrasting
confidence: 43%
“…Further studies are necessary to characterize the COX deficiency affecting patients 4, 6, and 7. However, we have confirmed that SURF1 mutations are responsible for Leigh syndrome associated with severe COX deficiency (12) and found a new phenotype of late Leigh syndrome associated with SURF1 mutations never described previously (2,3,8,13). …”
supporting
confidence: 82%
“…We selected three known missense mutations in SURF1 LS patients that result in G 124 E, I 246 T, and Y 274 D substitutions in SURF1 (31,39). Gly124 and Tyr274 are conserved residues in SURF1 orthologs, whereas Ile246 is a conserved hydrophobic residue.…”
Section: Characterization Of Human Surf1 Missense Mutations In the Yementioning
confidence: 99%